Synthesis of substituted CaFeO₃ perovskite catalysts with series B-site active phases for caffeine micropollutants' oxidative degradation - Alrozi, Rasyidah (2025)
In recent years, substituted perovskite with a general formula of ABB'Cb is considered as promising type of ceramic metal oxide heterogeneous catalyst for oxidative degradation of emerging micropollutants. The variation of B-site metal cation substitution in the perovskite structure led to a significant change in the overall catalytic performance of the resulting catalysts. However, the substitution of molybdenum (Mo), copper (Cu) and cobalt (Co) as an active phase for the B-site of CaFeCb for micropollutants' oxidative degradation in non-irradiation-assisted AOP remain unexplored. Hence, this research work aims to investigate the functional role of partially substituted B-site cations (Mo, Cu, Co) as an alternative type for B-site active phase towards modulation of resultant catalytic reactivity of substituted CaMFeCb (M = Mo, Cu, Co) perovskite catalyst. The partially substituted CaMFeCb (M = Mo, Cu, Co) perovskite catalyst was synthesized via modified EDTA citric acid complexation method. Then, a series of the selected high-performance substituted CaMxFei-x03 were synthesized by varying the B-site composition loading (x = 0, 0.2, 0.4, 0.6, 0.8). The catalytic performance of resultant catalysts was evaluated in oxidative degradation using caffeine solution as a model micropollutant. The perovskite catalysts were characterized using x-ray diffraction, field emission scanning electron microscopy, energy dispersive x-ray spectroscopy, nitrogen sorption analysis, oxygen temperatureprogrammed desorption, hydrogen temperature-programmed reduction, x-ray photoelectron spectroscopy, and electrochemical impedance spectroscopy. The reusability test and mineralization efficiency in the presence of optimum B-site composition loading (CaMxFei-xCb) was carried out at optimum operational conditions for caffeine degradation. The mechanism and degradation pathways of caffeine in the presence of optimum substituted CaMxFei-x03 were elucidated. The substituted CaCuFeCb exhibited the highest caffeine degradation (38%) within 4 hr of reaction compared to other partially substituted active phases. The high reducibility of copper/iron ions and decent electron mobility within the structure of substituted CaCuFeCb catalyst in the presence of H2O2 enables fast redox cycling of the active sites during catalysis. The optimum B-site composition loading of the perovskite was found at CaCuo.2Feo.8O3, which exhibited 66% caffeine degradation. Interestingly, the low amount of oxygen vacancies presence within the CaCuo.2Feo.8O3 perovskite structure led to a faster rate of electron transfer, thereby enhancing the redox cycling between =Fe2+/=Fe3+ and =Cu+/=Cu2+. This behaviour effectively promotes the activation of H2O2 in generating reactive »OH radicals during heterogeneous catalysis. The optimum operational conditions were proposed at 10 mg L"1 caffeine, 0.1 g L"1 catalyst, pH 3, 22 mM H2O2 and T = 27°C, with the highest caffeine degradation at 100% within 4 hr of reaction. It is noteworthy that the degradation efficiency of caffeine decreased slightly in the second cycle and then remained at -98% within five cycles of reactions. Nevertheless, caffeine was mineralized by the average of -30% within 4 hr in every cycle, despite the significant caffeine degradation performance. The proposed mechanism for caffeine degradation revealed that the oxygen vacancies facilitate facile Fe/Cu redox cycle by regenerating the active sites (=Fe2+ and =Cu+) within the CaCuo.2Feo.8O3 catalyst's structure. Detailed plausible caffeine degradation pathways were proposed based on the presence of intermediates compounds (N-N'-Dimethyl urea, methylparabanic acid and 1,7-Dimenthylxanthin) that were detected during catalysis prior to complete mineralization.